How Prior Knowledge Affects Word Identification and Comprehension - Priebe, Sarah J. (2011)
While prior knowledge of a passage topic is known to facilitate comprehension, little is known about how it affects word identification. We examined oral reading errors in good and poor readers when reading a passage where they either had prior knowledge of the passage topic or did not. Children who had prior knowledge of the topic were matched on decoding skill to children who did not know the topic so that the groups differed only on knowledge of the passage topic. Prior knowledge of the passage topic was found to significantly increase fluency and reduce reading errors, especially errors based on graphic information, in poor readers. Two possible mechanisms of how prior knowledge might operate to facilitate word identification were evaluated using the pattern of error types, as was the relationship of errors to comprehension. Implications of knowledge effects for assessment and educational policy are discussed.